Real-time on-campus public transportation monitoring system - Saad, Sarah Aimi; Hisham, Amirah 'Aisha Badrul; Ishak, Mohamad Hafis Izran; Fauzi, Mohd Husaini Mohd; Baharudin, Muhammad Ariff; Idris, Nurul Hawani (2018 IEEE 14th International Colloquium on Signal Processing & Its Applications (CSPA), 2018)
Real-time update is very important in Advanced Public Transportation System (APTS). However, due to the lack of information on the bus's estimated time of arrival (ETA), current location and occupancy (number of seats available) commuters are reluctant to use public transport. The study in this paper focuses on developing a bus tracking system that can track, display the location of the bus in real time and estimate the bus arrival time to the next bus stop. Monitoring system that consists of tracking device and web-based application for monitoring purposes are developed. GPS-based tracking device is used as location tracking mechanism and the location is reported for every 1 second to cloud database. Web application is developed as the graphical user interface (GUI) to assist user in monitoring real-time location of the bus and plan their journey based on information provided such as bus routes, bus stop number and bus arrival time. The updated location of the bus is plotted into Google Maps. Thus, based on result it was found that the proposed method is able to track and monitor the real-time location of the bus and able to estimate the bus's arrival time to the next bus stop.